Temperature dependence of the non-local spin Seebeck effect in YIG/Pt nanostructures - Kathrin Ganzhorn; Tobias Wimmer; Joel Cramer; Richard Schlitz; Stephan Geprägs; Gerhard Jakob; Rudolf Gross; Hans Huebl; Mathias Kläui; Sebastian T. B. Goennenwein (AIP Advances, 2017)
We study the transport of thermally excited non-equilibrium magnons through the ferrimagnetic insulator YIG using two electrically isolated Pt strips as injector and detector. The diffusing magnons induce a non-local inverse spin Hall voltage in the detector corresponding to the so-called non-local spin Seebeck effect (SSE). We measure the non-local SSE as a function of temperature and strip separation. In experiments at room temperature we observe a sign change of the non-local SSE voltage at a characteristic strip separation d0, in agreement with previous investigations. At lower temperatures however, we find a strong temperature dependence of d0. This suggests that both the angular momentum transfer across the YIG/Pt interface as well as the transport mechanism of the magnons in YIG as a function of temperature must be taken into account to describe the non-local SSE.